Factors Influencing Maternal Stress during Infant's NICU Stay in a Tertiary Care Center, South Kerala, India: A Cross-sectional Study - Chris Placid; Jacob Abraham (JCDR Research and Publications Pvt. Ltd., 2024)
Introduction: Recent advances in neonatal medicine have helped sick babies survive. However, the birth of a baby needing Neonatal Intensive Care Unit (NICU) stay may be a significant source of stress for mothers. Aim: To assess the maternal stress level perceived due to an infant's NICU stay and the factors influencing this stress. Materials and Methods: The present cross-sectional study was conducted in the NICU of Pushpagiri Institute of Medical Sciences and Research Centre, Thiruvalla, Kerala, India, between March 2021 and September 2021. The study included 74 mothers of infants requiring at least five days of NICU stay. The stress levels were recorded using the Parental Stressor Scale: NICU (PSS:NICU) questionnaire, which included 27 items under three stressor domains: Sights and Sounds (SS), Parental Role Alteration (PRA), and looks and behaviour of the baby. Data were statistically analysed using the Mann-Whitney U test and Kruskal-Wallis tests. Results: In the study group, 33 (45%) mothers experienced moderate stress, 18 (24%) experienced a high level, and the remaining 23 (31%) experienced only low-level stress. The overall maternal stress perceived in the study group was found to be at a moderate level with a mean of 3.36±0.67. Factors causing stress in mothers included prematurity, low birth weight, low 1st-minute Appearance, Pulse, Grimace, Activity and Respiration (Apgar) score, expressed breastfeeding, and previous experience with abortion. Conclusion: The present study found that mothers experienced moderate stress when their babies were admitted to the NICU. Significant stress was experienced by mothers when they were unable to perform their maternal duties.